ESTUDIO COMPARATIVO DEL DESARROLLO DE LA ALFABETIZACIÓN EN POBLACIONES DE EDUCACIÓN PRIMARIA Y PREESCOLAR - Mucio A. Romero Ramirez; Oscar Mariano Perez Matias; Miguel Bustos Diaz; Beatriz Morales Hernandez; Edgar A. Hernandez Flores (European Scientific Journal, ESJ, 2013)
A comparative study about early literacy of 33 children from elementary school and 27 children from kindergarden was carried out, applying the Instrumento de Observación de los Logros de la Lectoescritura Inicial (Escamilla, Andrade, Basurto y Ruíz, 1996). The purpose of the present work was to characterize the level of early literacy considering the knowledge of the language written in both groups. The groups were evaluated in the first two weeks of the month of September and of October of the school cycle 2011-2012. In the results it was observed that they were only significant differences in the identification of letters. The results are discussed in relation to the concept of early literacy.